A PET-CT study of the uptake of labeled aptamers [18F]FB-Gol1 and [18F]FB-GR20 in rat 101.8 glioblastoma model - Postnov, Andrey A.; Pronin, Igor N.; Vikhrova, Nina B.; Kalaeva, Diana B.; Pyzhik, Elena V.; Lipengolts, Alexey A.; Revishchin, Alexander V.; Dzarieva, Fatima M.; Sliman, Yahya A.; Golovin, Andrey V.; Korshun, Vladimir A.; Brylev, Vladimir A.; et al. (Frontiers in Oncology, 2025)
Background/ObjectivesThe ability to predict the values of immunohistochemical (IHC) biomarkers noninvasively for brain tumors is an important diagnostic task, accelerating the medical decision-making process and reducing the burden on the patient. In this work, the epidermal growth factor receptor (EGFR) is considered as a biomarker, the expression of which is associated with accelerated division and proliferation of cancer cells. The aim of this work is to study the binding of [18F]FB-Gol1 and [18F]FB-GR20 aptamers to the rat 101.8 glioblastoma model using PET-CT.MethodsThe tissue model of rat 101.8 glioblastoma was transplanted to Wistar rats (n=14). Rats with developed tumors underwent successive PET-CT examinations with [18F]FB-Gol1, [18F]FB-GR20 and [18F]FDG (n=11 completed), followed each time by MRI study (T1, T2, T1 with contrast enhancement). Time activity curves for both aptamers were analyzed. After the animals were euthanized, glial tumor tissue was taken for IHC tests to confirm EGFR expression.ResultsBoth [18F]FB-Gol1 and [18F]FB-GR20 were captured by the tumor within the first minutes after i/v administration. During one hour the accumulation in the tumor fell down to a quarter of the initial level. Both radiotracers showed no apparent signal in healthy tissue. The standardized maximum uptake value in the tumor was SUVt=0.44 ± 0.22 and 0.43 ± 0.20 for [18F]FB-GR20 and [18F]FB-Gol1, respectively. The metabolic volume of [18F]FB-GR20 and [18F]FB-Gol1 was also similar, 0.069 ± 0.056 cm3 versus 0.064 ± 0.053 cm3. At the same time, the metabolic volume of the tumor, measured by PET, turned out to be less than the volume of contrast enhanced tumor tissue on MRI and partially did not coincide with it in space. The radioactive label 4-[18F]-fluorobenzylazide alone injected separately does not accumulate in the tumor. Immunohistochemical analysis showed the presence of EGFR expression in rat 101.8 glioblastoma samples taken from animals.ConclusionsThis study demonstrates that both [18F]FB-Gol1and [18F]FB-GR20 radiopharmaceuticals bind to the rat 101.8 glioblastoma and may serve as promising candidates for the development of a diagnostic radiotracers for selective diagnosis of EGFR expression in glial tumors.